2004
DOI: 10.4049/jimmunol.173.11.6542
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A Critical Role for CD70 in CD8 T Cell Priming by CD40-Licensed APCs

Abstract: The CD154/CD40 interaction is an important pathway of CD4 T cell help for CD8 T cell responses. In this study, we address the role of CD70, a member of the TNF superfamily and the ligand for the T cell costimulatory receptor CD27, in CD40-mediated priming of CD8 T cells. Using an agonistic anti-CD40 mAb to mimic the CD154/CD40 interaction we demonstrate that the priming of OT-I TCR transgenic or endogenous mouse OVA-specific CD8 T cells is critically dependent on CD70/CD27 interaction. CD70 blockade inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
125
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 25 publications
10
125
2
1
Order By: Relevance
“…Interestingly, the requirement for 4-1BB costimulation during the primary response to influenza virus is greater during infection with a more virulent strain of virus, consistent with the higher expression of 4-1BB on activated T cells from mice bearing a higher viral load (13). Although the lack of CD27 signaling results in suboptimal CD8 T cell responses (12,(14)(15)(16)(17), deliberate triggering of CD27 by administration of soluble rCD70 (18) or through transgenic expression of CD70 on DCs (19) prevents tolerance induced by injection of a peptide Ag and allows the generation of a population of effector and memory CD8 T cells. Similarly, 4-1BB triggering was shown to prevent peptide-induced CD8 T cell tolerance (20) and augment effector and memory responses following peptide or DC immunization (21)(22)(23).…”
mentioning
confidence: 72%
“…Interestingly, the requirement for 4-1BB costimulation during the primary response to influenza virus is greater during infection with a more virulent strain of virus, consistent with the higher expression of 4-1BB on activated T cells from mice bearing a higher viral load (13). Although the lack of CD27 signaling results in suboptimal CD8 T cell responses (12,(14)(15)(16)(17), deliberate triggering of CD27 by administration of soluble rCD70 (18) or through transgenic expression of CD70 on DCs (19) prevents tolerance induced by injection of a peptide Ag and allows the generation of a population of effector and memory CD8 T cells. Similarly, 4-1BB triggering was shown to prevent peptide-induced CD8 T cell tolerance (20) and augment effector and memory responses following peptide or DC immunization (21)(22)(23).…”
mentioning
confidence: 72%
“…Concerning dendritic cell (DC) implication, it has been shown very recently by two independent teams an involvement of CD70 expressed on activated DC in the induction of CD8 þ Tcell responses and an interaction of CD40L and CD70 costimulatory molecules pathways leading to CD8 þ T-cell priming by antigen presenting cells (APCs). Taraban et al 21 showed that CD70 expression is induced on APCs by CD40 and stimulates CD8 þ T-cells expansion via CD27. On the other hand, Bullock et al 22 confirm this previous study by showing a correlation between CD70 expression on DC and their capacity to induce CD4 þ T-cell-independent expansion of CD8 þ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, CD4 + T cells expressing CD40L may directly deliver help to CD8 + T cells [7]. Besides the CD40-CD40L interaction, other receptor-ligand interactions such as the CD27-CD70 interaction may be important for generating functional CD8 + memory T cells [12]. In addition, soluble signals may be involved in CD8 + T cell formation.…”
mentioning
confidence: 99%